2022
DOI: 10.3390/biomedicines10102498
|View full text |Cite
|
Sign up to set email alerts
|

How Risk Factors Affect Head and Neck Squamous Cell Carcinoma (HNSCC) Tumor Immune Microenvironment (TIME): Their Influence on Immune Escape Mechanisms and Immunotherapy Strategy

Abstract: Most head and neck squamous cell carcinomas (HNSCCs) are caused by lifestyle, such as cigarette smoking, or by viruses, such as human papillomavirus (HPV) and Epstein–Barr virus (EBV). HNSCC remains a clinical challenge, notwithstanding the improvements observed in the past years, involving surgery, radiotherapy, and chemotherapy. Recurrent/metastatic (R/M) disease represents an unmet clinical need. Immunotherapy has improved the prognosis of a small proportion of these patients, but most still do not benefit.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 114 publications
0
6
0
Order By: Relevance
“…This phenomenon is known as cancer immunoediting. Unfortunately, many human cancers of various origin have developed biologically proven escape mechanisms from immune surveillance, which may affect the unlimited growth of tumour cells and contribute to the ineffectiveness of modern forms of immunotherapy, i.e., therapy based on immune checkpoint blockade, therapeutic vaccines, adoptive T cell therapy, combination therapies and treatment targeting immunocompetent suppressive cells [ 324 , 325 , 326 , 327 , 328 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is known as cancer immunoediting. Unfortunately, many human cancers of various origin have developed biologically proven escape mechanisms from immune surveillance, which may affect the unlimited growth of tumour cells and contribute to the ineffectiveness of modern forms of immunotherapy, i.e., therapy based on immune checkpoint blockade, therapeutic vaccines, adoptive T cell therapy, combination therapies and treatment targeting immunocompetent suppressive cells [ 324 , 325 , 326 , 327 , 328 ].…”
Section: Resultsmentioning
confidence: 99%
“…The development of new therapeutic strategies in cancer immunotherapy is directly related to the growing knowledge of the cancer immunity cycle, which constitutes the steps for the effective elimination and inhibition of tumour cells by immunocompetent cells, such as tumour infiltrating lymphocytes (TILs) and circulating different subpopulations of immunocompetent cells, such as neutrophils, cancer-associated macrophages (TAMs/MФ), cancer-associated fibroblasts (CAFs), regulatory T cells (CD4 + CD25 + Foxp3 + T regs ), cytotoxic CD3 + CD8 + T cells (CTLs) and CD3 + CD4 + T helper type ½/9/17 (Th 1 /Th 2 /Th9/Th 17 ) lymphocytes, T follicular helper cells (Tfh), CD56 dim /CD16 bright activated natural killer cells (NK) as well as carcinoma-associated fibroblasts (CAFs), myeloid-derived suppressor cells (MDSCs) and tumour-associated macrophages (M1/M2 TAMs). The cancer immunity cycle comprises the following stages: (A) immunogenic cell death and tumour antigen release from the neoplastic cells, (B) antigen processing and presentation by antigen presenting cells (APCs), i.e., mature dendritic cells (DCs) to naïve immune cells in tumour-draining lymph nodes and activation of CD4 + Th cells, (C) immunocompetent T cell priming and activation of CD4 + Th-cells and subsequently effector CD8 + T cells (CTLc) in the local lymph nodes, (D) displacement of T cells to the TME via the blood stream and infiltration to the tumour, (E) recognition of tumour cells by immune cells, CD8 + T cells (CTLc), (F) T cell mediated immune response, tumour cell recognition and initiation of cytotoxicity (killing of cancer cells) [ 50 , 324 , 325 , 326 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although patients with CPS greater than or equal to 1 had a higher MPR rate than those with CPS less than 1, the difference between them was not statistically significant. Other biomarkers validated in solid tumor, including TMB and TIME 36 , 37 , were also tested in our trial, but we found insufficient evidence.…”
Section: Discussionmentioning
confidence: 98%
“…New studies have shown that expression of NF-κB proteins is often correlated with the suppression of immune responses fighting against tumors. Regulatory cells, like Treg cells (which are activated by NF-κB), can inhibit the antitumor immune response if they are concentrated in the tumor [ 68 , 69 ]. As mentioned, cancer cells adopt several mechanisms to maintain survival, escape from the immune system, and suppress effector cells that would otherwise kill them within the tumor microenvironment.…”
Section: The Role Of Nf-κb In Cancer Progressionmentioning
confidence: 99%